Decision making : a psychophysics application of network science, Center for Nonlinear Science, University of North Texas, USA, 10-13 January 2010 - Grigolini, Paolo; West, Bruce J. (Studies of nonlinear phenomena in life sciences ;, 2011)
This invaluable book captures the proceedings of a workshop that brought together a group of distinguished scientists from a variety of disciplines to discuss how networking influences decision making. The individual lectures interconnect psychological testing, the modeling of neuron networks and brain dynamics to the transport of information within and between complex networks. Of particular importance was the introduction of a new principle that governs how complex networks talk to one another - the Principle of Complexity Management (PCM). PCM establishes that the transfer of information fr.